Pengaruh Tingkat Kecemasan Terhadap Waktu Mobilisasi Dini Pada Pasien Post-Operasi Sectio Caesarea Dengan Metode Eracs - Pitono, Arie J.; Tentry Fuji Purwanti, Tentry Fuji Purwanti; Riswan , Aris (Syntax Corporation, 2025)
Recently, sectio caesarea surgery with the ERACS (Enhanced Recovery After Cesarean Surgery) method is becoming a trend among the public because it is believed to reduce pain after surgery and also allow for a faster recovery process. Early mobilization is one of a series of ERACS methods, where in less than 24 hours patients are encouraged to have carried out mobilization. The patient can lift the leg within 2 hours after anesthesia. However, several factors are thought to affect the mobilization time, one of which is the level of anxiety. This study aims to determine the effect of anxiety level on early mobilization time in post-operative sectio caesarea patients using the ERACS method. This study used a cross sectional study design with a sample of 100 elective post-operative serctiro caersarera patients aged 25-35 years. Sampling was done using accidental sampling techniques. The results of the study found that as many as 41% of respondents experienced moderate levels of anxiety, the median time of early mobilization was 120 minutes, and there was a difference in early mobilization time in the mild, moderate, and severe levels of anxiety with a p value of < 0.001 in the Kruskal Wallis test and a p value of < 0.001 in the three post-hoc tests using the Mann-Whitney test. The conclusion of this study is that there is a difference in the time of early mobilization in various types of cercermasir in post-operative serctiro caersarera and ErRACS patients.